Characterization of corneal stromal stem cells with the potential for epithelial transdifferentiation - Hashmani, Khurram; Branch, Matthew James; Sidney, Laura E.; Dhillon, Permesh Singh; Verma, Megha; McIntosh, Owen Douglas; Hopkinson, Andrew; Dua, Harminder Singh (BioMed Central, 2013)
Introduction: The corneal stroma is being increasingly recognized as a repository for stem cells. Like the limbal and endothelial niches, stromal stem cells often reside in the peripheral cornea and limbus. These peripheral and limbal corneal stromal cells (PLCSCs) are known to produce mesenchymal stem cells in vitro. Recently, a common corneal stromal and epithelial progenitor was hinted at. This study aims to examine the stem cell potential of corneal stromal cells and to investigate their epithelial transdifferentiation ability.